Potential Role of Plant Growth Regulators in Administering Crucial Processes Against Abiotic Stresses - Sabagh, Ayman EL (2021)
Plant growth regulators are naturally biosynthesized chemicals in plants that influence physiological processes. Their synthetic analogous trigger numerous biochemical and physiological processes involved in the growth and development of plants. Nowadays, due to changing climatic scenario, numerous biotic and abiotic stresses hamper seed germination, seedling growth, and plant development leading to a decline in biological and economic yields. However, plant growth regulators (PGRs) can potentially play a fundamental role in regulating plant responses to various abiotic stresses and hence, contribute to plant adaptation under adverse environments. The major effects of abiotic stresses are growth and yield disturbance, and both these effects are directly overseen by the PGRs. Different types of PGRs such as abscisic acid (ABA), salicylic acid (SA), ethylene (ET), and jasmonates (JAs) are connected to boosting the response of plants to multiple stresses. In contrast, PGRs including cytokinins (CKs), gibberellins (GAs), auxin, and relatively novel PGRs such as strigolactones (SLs), and brassinosteroids (BRs) are involved in plant growth and development under normal and stressful environmental conditions. Besides, polyamines and nitric oxide (NO), although not considered as phytohormones, have been included in the current review due to their involvement in the regulation of several plant processes and stress responses. These PGRs are crucial for regulating stress adaptation through the modulates physiological, biochemical, and molecular processes and activation of the defense system, upregulating of transcript levels, transcription factors, metabolism genes, and stress proteins at cellular levels. The current review presents an acumen of the recent progress made on different PGRs to improve plant tolerance to abiotic stress such as heat, drought, salinity, and flood. Moreover, it highlights the research gaps on underlying mechanisms of PGRs biosynthesis under stressed conditions and their potential roles in imparting tolerance against adverse effects of suboptimal growth conditions.